A Study of Air Pollution In Two Cities of Haryana: Impact of Growing Industries on Air Pollution in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Air pollution is a major problem not only in Haryanabut all over world. Now a days due to growing industries Haryana is heavilypolluted which is disturbing the ecological balance. Although pollution is asold as man himself but awareness about it is only recent. Air has never beenpure, foreign substances have been present in air all the time. The mainpollutants in air are sulfur di oxide, nitrogen di oxide, SPM, RPM, and becausethe numbers of industries in Haryana are increasing day by day due toincreasing population the amount of these pollutants are also increasing. Whenthe monitoring was conducted in two cities namely Hisar and Gurgaon in Haryana wefound that in both the cities the concentration of so2 was with in prescribedlimits of CPCB. however the no2 values cross the maximum limits at vehiculararea in Hisar. Highest values of SPM, RPM was at Gurgaon which is a seriousconcern.